Biochemical Changes During Salt Fermentation of Pangasius hypophthalmus (Sauvage, 1878) - Praveen Kumar, G.; Balange, A. K.; Martin Xavier, K. A.; Nayak, B. B.; Sanath Kumar, H. (Fishery Technology, 2017)
The suitability of Pangasius hypophthalmus as a raw material for salt fermentation and changes during 135 days was analysed. Pangasius steaks were fermented in food grade PVC jar and biochemical parameters such as pH, salt, thiobarbutric acid reactive substances (TBARS), free Î±-amino nitrogen (FAN), moisture and ash content were analysed. The moisture content of Pangasius had shown a slight increase during fermentation from 54.9% (0th day) to 56.67 (135th day). Ash content recorded an increase from 11.98% on 1st day to 18.17% (135th day). Salt content of Pangasius steaks has increased significantly (p0.5) during fermentation. TBARS content recorded an increase till 75th day and decreased continuously till maturation. The FAN registered an increase from 44.71 mg% (0th day) to 92.86 mg% (135th day).The moisture, pH, ash, salt, TBARS, FAN in the final matured fermented product were 56.67%, 5.93%, 18.17%, 14.43% and 0.21 mg malonaldehyde kg-1 of fat and 92.86 mg% respectively. Therefore, it was concluded that Pangasius developed a firm consistency and characteristic flavour and taste over 135 days of maturation.